PENGARUH KEPEMIMPINAN,MOTIVASI, BUDAYA ORGANISASI DAN KEPUASAN TEIUIADAP KINERJA ORGANISASI (Studi pada Kelompok Tani Madurejo Prambanan) - Junaidi Affan (Solusi: Jurnal Kajian Ekonomi dan Bisnis, 2015)
This study aims to determine the effect of variables of leadership , motivation, organizational culture and the satisfaction of both partially and simultaneously on the performance of a group of cattle in the organization Modurejo The total sample of 63 people, using the data questionnaire with a scale Linkert were analyzed with SPSS version 20.0. The results of the analysis of partial leadership, organizational culture and satisfaction significant positive effect on performance. Variable motivation for significant negative effect on performance. Regression analysis together there are significant positive effect on performance. The contribution of leadership, motivation, organizational culture and satisfaction with the performance of 96.9 %. The rest is beyond this study